(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the article the features of formation of the tax burden on activities of economic entities in terms of reforming the financial system of Ukraine The concept of the tax burden and its status in Ukraine. The dynamics of the amount tax burden in Ukraine and provide recommendations for optimizing the tax burden on businesses